The role of lymphatic endothelial cell metabolism in lymphangiogenesis and disease - Simeroth, Summer; Yu, Pengchun (Frontiers in Cardiovascular Medicine, 2024)
Lymphatic endothelial cells (LECs) line lymphatic vessels, which play an important role in the transport of lymph fluid throughout the human body. An organized lymphatic network develops via a process termed “lymphangiogenesis.” During development, LECs respond to growth factor signaling to initiate the formation of a primary lymphatic vascular network. These LECs display a unique metabolic profile, preferring to undergo glycolysis even in the presence of oxygen. In addition to their reliance on glycolysis, LECs utilize other metabolic pathways such as fatty acid β-oxidation, ketone body oxidation, mitochondrial respiration, and lipid droplet autophagy to support lymphangiogenesis. This review summarizes the current understanding of metabolic regulation of lymphangiogenesis. Moreover, it highlights how LEC metabolism is implicated in various pathological conditions.